2015
DOI: 10.1111/cod.12328
|View full text |Cite
|
Sign up to set email alerts
|

Contact dermatitis as an adverse reaction to some topically used European herbal medicinal products – Part 2: Echinacea purpurea–Lavandula angustifolia

Abstract: SummaryThis review focuses on contact dermatitis as an adverse effect of a selection of topically used herbal medicinal products for which the European Medicines Agency has completed an evaluation up to the end of November 2013 and for which a Community herbal monograph has been produced. Part 2: Echinacea purpurea Moench-Lavandula angustifolia Mill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 99 publications
0
20
0
1
Order By: Relevance
“…In Patch-testing for contact allergy to lavender oil addition, photoallergic contact dermatitis to lavender oil in topical ketoprofen preparations has been reported (37). Also, the interest in essential oils, such as lavender oil, in alternative medicine is increasing (2,3,5) and several studies show that exposure to botanically derived products and natural drugs, based on plant extracts and essential oils can be causes of allergic contact dermatitis (38)(39)(40). Thus, allergic contact dermatitis to essential oils mirrors the broad spectrum of use of these plant extracts, and exposures beyond aromatherapy and fragranced cosmetic products are of importance.…”
Section: Discussionmentioning
confidence: 99%
“…In Patch-testing for contact allergy to lavender oil addition, photoallergic contact dermatitis to lavender oil in topical ketoprofen preparations has been reported (37). Also, the interest in essential oils, such as lavender oil, in alternative medicine is increasing (2,3,5) and several studies show that exposure to botanically derived products and natural drugs, based on plant extracts and essential oils can be causes of allergic contact dermatitis (38)(39)(40). Thus, allergic contact dermatitis to essential oils mirrors the broad spectrum of use of these plant extracts, and exposures beyond aromatherapy and fragranced cosmetic products are of importance.…”
Section: Discussionmentioning
confidence: 99%
“…14 Clarifying the nature of an exposure is further complicated by the variable nomenclature used in product labelling. 11 Over the period of this study, four different lavender allergen preparations were in use. The historical details of how this situation developed are unclear; however, the basic rationale was to broaden the testing to reflect the diverse forms of potential lavender exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Formal studies examining the allergenicity of lavender oil in humans have produced variable results, and it has been suggested that this can be explained by the effect of autoxidation, leading to the generation of more potent contact allergens. 11 Both linalool and linalyl acetate are only weakly allergenic when present in their pure form; however, autoxidation leads to the production of potent sensitizers, in particular hydroperoxides. [15][16][17][18] It is thus advised that testing be performed with the oxidized forms of these chemicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanto o escore de intensidade de odor quanto o de aceitação do odor do OML foram maiores ao se comparar com os demais óleos avaliados (p<0,05), desta forma é possível que esta fragrância tenha obtido os maiores escores pelas suas notas olfativas serem consideradas como muito conhecidas popularmente, por sua constante aplicação em produtos cosméticos, de higiene pessoal, perfumaria, na terapia, tornando-a importante comercialmente (GANGEMI et al, 2015).…”
Section: Discussionunclassified